Digital Service Orchestration and Customs Performance: The Mediating Role of Process Integration in Indonesia - Dodi Hariyanto; Agus Purnomo; Maniah Maniah (Politeknik Siber Cerdika Internasional, 2026)
Background: Digital transformation in Indonesia’s public sector is a strategic effort to improve efficiency, transparency, and quality of customs services through Indonesia National Single Window (INSW). However, increasing digital transaction volumes has not been matched by optimal customs performance, as reflected in high dwelling time compared to global standards. Objective: This study examines the effect of Digital Service Integration (ILD), Regulatory and Process Synchronization (SRP), and Service Information Connectivity (KIP) on Customs Service Performance (KLK), with Digital Process Integration (IPD) as a mediating variable. Method: A quantitative explanatory design was applied using PLS-SEM. Data were collected from 206 respondents consisting of exporters, government officials, and logistics service providers involved in INSW services. Results: Findings show that ILD, SRP, and KIP significantly and positively influence IPD and KLK. The model demonstrates strong explanatory power (R² KLK = 0.782; R² IPD = 0.714). KIP is the strongest predictor of KLK (β = 0.342, p < 0.001), while IPD significantly mediates all relationships. Conclusion: The study confirms that improving customs service performance requires not only digitalization but also integrated digital processes, regulatory harmonization, and real-time interoperable data systems across institutions.